Análise da subjetividade materializada em contos de fadas produzidos por crianças no setting psicanalítico - Menezes, Renata de Lourdes Costa de (2014)
Dating back to ancient times, the fairy tale, more fun that children, has played, in child psychoanalysis, the role of a therapeutic tool. That's because this literary genre promotes a safe atmosphere for the child, in writing its own history, expresses their emotional experiences and to develop their inner conflicts through a symbolic and fictional universe. The aim of this study is, therefore, to identify the subjective aspects embodied in fairy tales written by children in psychoanalytic setting from the theoretical-epistemological and methodological perspective of the Sociodiscursive Interactionism (ISD). We start, therefore, the assumption that, in writing in psychoanalytic session, the child mobilizes a set of language abilities that become scenario of projections psycho-affective and thus are able to reveal the author's subjectivity. To substantiate our study, we conducted a documentary research, qualitative approach, in which we analyzed fairy tales written by childrenduring psychoanalytic treatment in a Psychology Clinical School of the Federal University of Paraíba. Still, were consulted information, journaled clinical, obtained in interview with parents or legal guardians, about the manifest symptoms and life situation personal, social and family of the child. We build our analysis in operations planning language proposed by Machado and Bronckart (2009), including the thematic content, the constitution and the organizational layout of the text and the enunciative mechanisms. Finally, we proposed a reading on the semantics of action guided by the analyzes, discussed earlier. Our results indicate that the psychotherapeutic context proved to be disparate environment by making possible that children express, themselves, authentically, their internal dilemmas; that the unconscious formations also underlie the actions of language; that the this unconscious formations, embodied in action language, are so dependent internalization as representation of experience as the rational construct; that the social universe and the intrinsic reality of the children are in close conjunction; and that there is a subjective richness underlying fairytales produced in the core of a psychotherapeutic process. Thus, the overall comprehensive methodology proposed by ISD as a tool capable of stripping the unconscious impulses, from the structural and functional characteristics of a text; and, likewise, psychoanalytic interpretations revealed, to the ISD, one possible way of reading the affective and emotional dimensions of the enunciator, through its textual production.